Performance evaluation of available strains of Nile tilapia (Oreochromis niloticus) fed commercial and locally-made feeds in the Democratic Republic of the Congo - Yossa, Rodrigue; Basiita, R.K.; Namegabe, J.M.; Trinh, T.Q.; Matempa, D.; Manzwanzi, P.; Bwamayama, L.; Cole, Steven M.; Matungulu, P.; Dontsop Nguezet, Paul M.; Vanlauwe, Bernard; Ndavi, M.; et al. (MDPI, 2023)
The performance of two strains of Nile tilapia (the Nyakabera and Lake Kivu) fed a commercial feed or either a fishmeal-based or a fishmeal-free feed formulated using local ingredients was evaluated for 99 days in Bukavu, eastern highlands of the DR Congo (Experiment 1). Strain × feed interaction was significant (p < 0.05) for final body weight (FBW) and condition factor (CF). Growth of both strains was best with the commercial feed. Fish-meal free formulated feed resulted in similar or better fish growth than a local fishmeal-based formulated feed depending on the strains. Lake Kivu strain had significantly (p < 0.05) higher FBW when fed the commercial and fishmeal-free feeds than the Nyakabera strain, but when fed the fishmeal-based feed the difference was not significant. The performance of the other three Nile tilapia strains (the GIFT-Congo Futur, GIFT-RATALBI and Tihange strains) fed a single commercial feed was evaluated for 84 days in Kinshasa, western lowlands of the DRC (Experiment 2). Male GIFT-Congo Futur and GIFT-RATALBI did not differ significantly (p > 0.05) in FBW and CF, but both performed better than the Tihange. FBW of the female GIFT-Congo Futur was significantly higher than that of the other two strains, while CF was not significantly (p > 0.05) different among strains in females.